A SURVEY OF STUDENTSâ LANGUAGE LEARNING STRATEGIES AND THEIR ENGLISH LEARNING ACHIEVEMENT IN SMA NEGERI 1 PALOPO - Muhammad, Iksan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2015)
The objectives of this research were: (1) To investigate the dominant language learning strategies (LLSs) used by the students in SMA Negeri 1 Palopo; (2) To investigate the dominant LLSs used by the high and low achiever students in SMA Negeri 1 Palopo; and (3) To investigate the correlation between the studentsâ dominant LLSs and their English achievement.This research involved 63 students that were chosen using cluster random sampling technique. The data that was obtained through SILL questionnaire and English achievement test were analyzed using descriptive statistics through SPSS software version 21.0.The findings revealed that the students use all of the six categories of LLSs given by Oxford (1990), and the most dominant used LLSs category by the students are metacognitive strategies (39.76%), followed by affective strategies (16.95%), while the least dominant used strategies by the students are social strategies (7.60%), followed by memory strategies (8.77%). The high achiever students dominantly use cognitive strategies (40%), followed by metacognitive strategies (30%), while the low achiever students dominantly use metacognitive strategies (42.22%), followed by affective strategies (16.67%). The Chi-square analysis reveals that accumulatively, there is no statistical correlation between the dominant categories of LLSs that the students use with their English achievement.